Direct Trifluoromethylthiolation of Unactivated C(sp3)H Using Silver(I) Trifluoromethanethiolate and Potassium Persulfate1. (23rd February 2015) - Wu, Hao; Xiao, Zhiwei; Wu, Junhui; Guo, Yong; Xiao, Ji‐Chang; Liu, Chao; Chen, Qing‐Yun
Abstract A practical and efficient method for the direct trifluoromethylthiolation of unactivated C(sp3)H bonds by AgSCF3/K2S2O8 under mild conditions is described. The reaction has a good functional‐group tolerance and good selectivity. Initial mechanistic investigations indicate that the reaction may involve a radical process in which K2S2O8 plays key roles in both the activation of the C(sp3)H bond and the oxidation of AgSCF3.